The Loyalty Measurement Problems of Travel Agencies' Customers in Poland - Michalska-Dudek, Izabela; Rapacz, Andrzej (Studia Oeconomica Posnaniensia, 2017)
The purpose of the article is to discuss the indicators for customer loyalty measurement and to analyse the loyalty level of travel agencies' customers in Poland. The review of subject literature allowed presenting the indicators for loyalty measurement and also the indicators for customer selection used for customer loyalty management. The realisation of the research goals was possible as a result of survey studies carried out among travel agencies' customers in Poland (N = 1151). The article presents the empirical research results of travel agencies' customers in Poland, which allowed their loyalty level assessment. The conducted analysis confirmed that travel agencies' customers in Poland represented loyal purchasers of tourist services. The presented research results have an application oriented importance and can be a useful source of information in the strategy development process for travel agencies that are operating on the market. Among the practical implications the respondents' suggestions, referring to the hidden possibilities, were indicated, which could result in their higher inclination towards recommending a given travel agency service to other people. They identify the potential sources of a competitive advantage, as well as the necessary directions of modifications in the analysed area.